Assessment of metallic pollution (Hg, Pb, Cd, Cu) of water and sediment in fish ponds located in a lowland in the city of Daloa - AKESSE Djamatche Paul Valery; DALOGO Kacou Alain Paterne; KOFFI Akissi Lydie Chantal; KOUADIO David Leonce (Chemical Review and Letters, 2022)
The Assessment of the metallic pollution of the water and sediment of four fish ponds located in the town of Daloa has been determined. To do this, water and sediment samples were taken from these ponds for the determination of Hg, Pb, Cd and Cu with the atomic absorption spectrophotometer. The results of the analysis show that the water quality of the various fish ponds is influenced by the variation of the physicochemical parameters and that these waters are vulnerable to organic and inorganic pollution. Moreover, these results also revealed Cu (5.039 mg.L-1) and Hg (5.191 mg.L-1) are the metals most accumulated in the waters of fish ponds, while for sediments we have Cu (708.909 mg.kg-1) and Pb (1.22 mg.kg-1). The order of preferential accumulation of ETM in the water of these ponds is as follows: [Cu]>[Hg]>[Pb]>[Cd]. That of the sediments is [Cu]>[Pb]>[Hg]>[Cd]. This shows that whatever the study matrix, Cu is the most predominant metal. On the other hand, the values of the Geo index did indeed show a high intensity of the pollution of the sediment of fish ponds by Hg and Cu. These two metals would therefore present risks of metallic bioaccumulation of living organisms in this environment due to their presence and their strong accumulation